THE IMPLEMENTATION OF LEGAL NORM AGAINST DRUGS ABUSE OF DOUBLE L PILLS AT TANJUNG PERAK PORT POLICE SURABAYA - Sumaryanto, Dr. A. Djoko; Sholehuddin, Dr. M.; Sugiharto, Dr.; Naibabo, Bryan (jfpublisher, 2024)
Legal norms are rules that regulate people's behavior based on good and bad values, and determine what is permissible, recommended, or mandatory in a social context to maintain order. Regarding drug abuse, such as Double L pills that are often used without a authorization, Indonesia's Health Law No. 17/2023 regulates sanctions for illegal pharmaceutical activities and violations of safety standards, with a maximum penalty of 12 years in prison and a fine of up to IDR 5 billion for serious cases. This research aims to understand and analyze the implementation of the law and criminal liability related to the abuse of dangerous drugs, especially double L pills, in the Tanjung Perak Port Police area of Surabaya. The research uses a normative juridical method with a statutory and case study approach. The legal materials used include primary, secondary, and tertiary materials, which are collected and analyzed in a qualitative method. The results are presented descriptively for the easy understanding of the readers. The Tanjung Perak Port Police Narcotics Unit enforces legal standards according to Indonesian Health Law No. 17/2023 and the Criminal Code, as seen in case No. 950/Pid.Sus/2024/PN Sby, where the defendant was charged under Article 436 and Article 145 of the same law. However, challenges such as limited personnel, inadequate facilities, low public awareness about drug laws, and the vast Surabaya area complicate efforts to control drug distribution networks effectively.